Penerapan Haar Cascade Classifier dalam Mendeteksi Wajah dan Transformasi Citra Grayscale Menggunakan OpenCV - S Yulina (Politeknik Caltex Riau, 2021)
Face detection applications on digital images are very necessary in the process of face recognizing. This application is widely used in various disciplines, one of them is computer vision such as biometric recognition systems, search systems, and security systems. Computer vision is a combination of artificial intelligence and machine learning. It can gain informations from image and video by using computer algorithms. Many previous studies have developed face detection applications with various algorithms with certain programming languages. The detection of an object is the most important part in computer vision. Determining an accurate face location is still a challenging task for researchers. The location of the face is the main step in computer vision to find the face part in the input image. Open Source Computer Vision Library (OpenCV) is software that allows open-source library containing supporting object detection that is easily accessed into the Java programming language. Haar cascade classifier is one of the algorithms used for object detection. This algorithm can convert an object quickly by taking the number of images in a square shape on an image. In this study, discussing the application of face detection in digital images using the Haar Cascade Classifier and the transformation of images into gray / grayscale images using the OpenCV library. The results in this study have 100% accuracy in input images that have objects in the frontal position.